Analysis Of Electronic Medical Records Implementation Using The Pieces Method At Balaraja Regional Hospital - Melani Aulia Mufida; Puteri Fannya; Dina Sonia; Daniel Happy Putra (Interdisciplinary Social Studies, 2025)
The advancement of information technology in the healthcare sector encourages hospitals to adopt Electronic Medical Records (EMR) systems to improve efficiency, accuracy, and service quality. This study aims to analyze the implementation of EMR at Balaraja Regional Public Hospital (RSUD Balaraja) using the PIECES framework (Performance, Information, Economy, Control, Efficiency, and Service). A descriptive qualitative method was employed, with data collected through observations and indepth interviews involving seven informants from the medical records unit. The results show that in terms of performance, the EMR system is responsive and supports staff tasks, although integration between systems remains a challenge. From the information aspect, the system is considered accurate and accessible, yet lacks automated data validation. Economically, the EMR system has improved resource efficiency and reduced long-term operational costs. In terms of control, data security is well managed through personal user accounts and system backups. The efficiency aspect reflects faster workflows and reduced manual processes. From the service perspective, the system enhances user satisfaction and convenience, though occasional technical issues still occur. This study recommends improving system integration and conducting continuous training to optimize EMR implementation at RSUD Balaraja.